Analysis of the dependence of economic growth on the level of higher education of the population within the EU cohesion regions - Votava, Michal; Lukavec, Martin, 1980-; Černá Silovská, Hana; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
This bachelor’s thesis analyses higher education in the context of economic growth. The aim is to identify and evaluate the connection between higher education and regional development. In the theoretical part, I analyse what education is and what it affects. Specifically, I am studying its’ effects on the regional economy and on the decline of manufacturing jobs. In the practical part, I am using panel data models, specifically the Pooled OLS, the Fixed effects and the Random effects regression models to quantify the correlation between education, GDP, disposable income, average temperature, variable coefficient of the average temperature and density of population. Besides this, I am examining the return of education comparing costs of education and future average earnings.
Vedoucí práce: Martin Lukavec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: veřejná správa a regionální rozvoj [obor bakal. práce]; bakalářské práce; bachelor's theses